Acceptance towards decriminalization of medical marijuana among adults in Selangor, Malaysia - Dapari, Rahmat; Mahfot, Mohd Hafizuddin; Mohd Nazan, Ahmad Iqmer Nashriq; Hassan, Mohd Rohaizat; Che Dom, Nazri; Syed Abdul Rahim, Syed Sharizman (Public Library of Science, 2022)
Introduction : The issue of decriminalization of medical marijuana has gained public attention globally due to the decisions of various governments in developed and developing countries who have decriminalized marijuana for medical purposes. The action was the result of the change in perception towards medical marijuana use, which is now believed to be safe, acceptable, and should be decriminalized. Due to the progress of modernization and the wide access to information, the change in perception towards medical marijuana seems to be inevitable and might have already permeated among the public in Malaysia. However, at the moment there is no baseline data to determine any of this claim. Objective : To determine the prevalence and factors associated with acceptance towards decriminalization of medical marijuana among adults in Selangor, Malaysia. Methodology: The study was a cross-sectional study conducted in year 2021 among 462 adults aged 18 years old and above in Selangor, Malaysia. The respondents were sampled using a multistage random sampling. The data was collected via self-administered questionnaires and has been analyzed using SPSS version 25. Result : More than half of the respondents in this study (64.7%) show acceptance towards the decriminalization of medical marijuana in Malaysia. The results of statistical tests indicate that there are significant associations between age (p < 0.001), gender (p = 0.005), ethnicity (p < 0.012), level of education (p < 0.011), employment status (p = 0.001), ever smoked (p < 0.001), given up smoking (p = 0.002), ever used substance (p < 0.001), current substance use (p < 0.001), given up substance (p < 0.001), exposure to medical marijuana-related content (p < 0.001), perceived risk associated with medical marijuana use (p < 0.001), perceived risk of harm of medical marijuana use (p < 0.001), and perceived approval of medical marijuana use (p < 0.001) with acceptance towards decriminalization of medical marijuana. The predictors for acceptance towards decriminalization of medical marijuana are perceived high approval of medical marijuana use (aOR = 7.023, p < 0.001, 95%CI = 3.534,13.955), perceived low risk of medical marijuana (aOR = 5.716, p < 0.001, 95%CI = 2.828,11.554), perceived low risk of harm from medical marijuana use (aOR = 3.480, p = 0.001, 95%CI = 1.702,7.114), current substance use (aOR = 2.264, p = 0.050, 95%CI = 1.001,5.118), and ever used substance (aOR = 2.005, p = 0.004, 95% CI = 0.054,0.576). Conclusion : The results of the survey show that the current acceptance level towards decriminalization of medical marijuana is considerably high. However, the acceptance is mainly among those who are exposed to the substance and those who perceive low risk of medical marijuana. Thus, a further exploration of this phenomenon is needed, especially by increasing the sample size and expanding the study location to other states.